1921
DOI: 10.1242/jcs.s2-65.260.589
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Shape of the Nucleus and its Determination

Abstract: Variations in the shape of the nucleus have been described in different animal cells. In addition, the following factors have been shown to be responsible for nuclear shape: (1) Surface tension : when this is equal over the surface of the nuclear membrane, the nucleus tends towards the spherical condition. When surface tension varies over the interface between nucleus and cytoplasm, nuclear polymorphism may result. (2) Mechanical deformation of the nucleus is common and may be due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…According to the literature, applying a force to the cell changes its elongation and orientation, which in turn induces deformation of the nucleus and changes its function [44,52]. Furthermore, deformation of the nucleus appears as a potential regulator of the genome function, with the effect that the cell shape information is carried through mechanical forces transmitted by the cytoskeleton to the gene expression [53]. As a consequence of cell shape deformation, the cytoskeleton produces a force to change the shape and size of the nucleus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, applying a force to the cell changes its elongation and orientation, which in turn induces deformation of the nucleus and changes its function [44,52]. Furthermore, deformation of the nucleus appears as a potential regulator of the genome function, with the effect that the cell shape information is carried through mechanical forces transmitted by the cytoskeleton to the gene expression [53]. As a consequence of cell shape deformation, the cytoskeleton produces a force to change the shape and size of the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the reason for the elongation of the cell and nucleus is the presence of a large number of free radicals and their effects on the cell and the consequent applied force on cytoskeletal actin filaments and myosin, which are supposed to control the morph ology of the cell and nucleus and can affect the expression of genes in response to changes in cell and nucleus shape. Cell deformation and cellular elongation ultimately lead to cellular damage and probably lead to cancer initiation due to the force exerted on actin fibers [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical forces profoundly influence cellular and nuclear morphology. The hypothesis that mechanical force can influence nuclear shape was posited by Champy and Carleton in the 1920s ( Champy and Carleton, 1921 ). Following this hypothesis, morphological adaptation of ECs to fluid shear stress was reported in the 1950s, and ECs were described to align in the direction of blood flow ( Altschul, 1954 ).…”
Section: Endothelial Integration Of Shear Stressmentioning
confidence: 99%
“…The nucleus is the control center of the cell, that is why we focus our attention on this organelle. Indeed, it has been shown that changes in cell shape results in modifications of nuclear shape and functions [7][8][9]. Cell shape changes in endothelial cells have been associated with nuclear shape remodeling [10] resulting in regulation of gene expression [11,12].…”
mentioning
confidence: 99%